2008
DOI: 10.1152/ajpcell.00528.2007
|View full text |Cite
|
Sign up to set email alerts
|

K restriction inhibits protein phosphatase 2B (PP2B) and suppression of PP2B decreases ROMK channel activity in the CCD

Abstract: We used Western blot analysis to examine the effect of dietary K intake on the expression of serine/ threonine protein phosphatase in the kidney. K restriction significantly decreased the expression of catalytic subunit of protein phosphatase (PP)2B but increased the expression of PP2B regulatory subunit in both rat and mouse kidney. However, K depletion did not affect the expression of PP1 and PP2A. Treatment of M-1 cells, mouse cortical collecting duct (CCD) cells, or 293T cells with glucose oxidase (GO), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The reduction in ROMK-like SK channel activity following inhibition of PP2B-cat could be reversed by coincubation with p38 and ERK inhibitors, suggesting MAPKs involvement in ROMK-like SK inactivation (51). As inhibition of PP2B-cat increases the phosphorylation of p38 and ERK, the authors concluded that ROS can inhibit the ROMK-like SK channel by reducing PP2B-cat activity (51). This would increase p38 and ERK phosphorylation, activating them, which would increase ROMK-like SK channel phosphorylation, inhibiting it.…”
Section: Role Of Nadph Oxidase In Apical Romk-like Sk Channel Regulationmentioning
confidence: 95%
See 3 more Smart Citations
“…The reduction in ROMK-like SK channel activity following inhibition of PP2B-cat could be reversed by coincubation with p38 and ERK inhibitors, suggesting MAPKs involvement in ROMK-like SK inactivation (51). As inhibition of PP2B-cat increases the phosphorylation of p38 and ERK, the authors concluded that ROS can inhibit the ROMK-like SK channel by reducing PP2B-cat activity (51). This would increase p38 and ERK phosphorylation, activating them, which would increase ROMK-like SK channel phosphorylation, inhibiting it.…”
Section: Role Of Nadph Oxidase In Apical Romk-like Sk Channel Regulationmentioning
confidence: 95%
“…Exogenous O 2 Ϫ or H 2 O 2 was found to reduce the expression of PP2B-cat (catalytic subunit) in M1 cells (51). Further, inhibition of PP2B-cat using cyclosporine A or FK-506 reduced apical ROMK-like SK channel activity (51).…”
Section: Role Of Nadph Oxidase In Apical Romk-like Sk Channel Regulationmentioning
confidence: 98%
See 2 more Smart Citations
“…9 This channel may be responsible for drug-induced hyperkalemia, because cyclosporin A (CsA), an immunosuppressant drug that causes hyperkalemia, inhibits the channel. 10,11 However, the mechanism by which CsA inhibits ROMK1 channels remains unclear. Our recent studies suggest that CsA stimulates the epithelial sodium channel (ENaC) through elevation of intracellular cholesterol.…”
mentioning
confidence: 99%